Investigating the implementation of a novel approach to alcohol screening and brief intervention in Mexico: a mixed-methods study using pseudo-patients - Fisher, Deborah A.; Grube, Joel W.; Lilliott-González, Liz; Elias, Marissa; Sturm, Robert; Ringwalt, Christopher L.; Miller, Ted R.; Cardenas Vargas, Elena; Achoki, Tom; Rizzo, Angela (Frontiers in Public Health, 2024)
Introduction Low- and middle-income countries bear disproportionate burdens from excessive alcohol consumption, yet have fewer resources to identify and intervene with risky drinkers. Low-cost screening and brief intervention (SBI) models offer a tool for addressing this health problem and reducing disparities. Methods In this mixed-methods study, trained pseudo-patients visited health clinics in Zacatecas, Mexico, where a novel SBI model was used with trained nonmedical health educators (HEs) conducting SBI in waiting areas. Pseudo-patients, who provided responses to the AUDIT-C screening items designed to trigger a brief intervention (BI), waited for HEs to engage them in an SBI encounter. Data on HEs’ behaviors, SBI components provided, and contextual characteristics were coded from audio recordings of the encounters using an SBI checklist and from pseudo-patient interviews. Results Quantitative analyses examined the consistency in pseudo-patients’ targeted AUDIT-C scores and those documented by HEs as well as the frequency of delivery of SBI components. Across 71 interactions, kappas between HEs’ scores and the targeted AUDIT-C scores ranged from 0.33 to 0.45 across AUDIT-C items; it was 0.16 for the total AUDIT-C. In 41% of interactions, the HEs recorded total AUDIT-C scores that accurately reflected the targeted scores, 45% were below, and 14% exceeded them. Analyses of checklist items and transcripts showed that HEs demonstrated desired interpersonal skills (attentive, empathetic, professional) and provided general information regarding risks and recommendations about reducing consumption. In contrast, personalized BI components (exploring pseudo-patients’ personal challenges and concerns about reducing drinking; making a plan) occurred much less frequently. Pseudo-patient interviews revealed contextual factors (noise, lack of privacy) that may have negatively affected SBI interactions. Discussion Using trained nonmedical persons to administer SBI holds promise to increase its reach. However, ongoing training and monitoring, prioritizing comprehensive BIs, eliminating contextual barriers, and electronic delivery of screening may help ensure high quality delivery.